DLL3 (delta like protein 3) expression correlates with stromal desmoplasia and lymph node metastases in medullary thyroid carcinomas. Issue 5 (February 2021) - Ingenwerth, Marc; Brandenburg, Tim; Führer-Sakel, Dagmar; Goetz, Moritz; Weber, Frank; Dralle, Henning; Schildhaus, Hans-Ulrich; Schmid, Kurt Werner; Theurer, Sarah
Abstract : Medullary thyroid carcinomas (MTC) are rare and aggressive neuroendocrine tumors of the thyroid. About 70% of MTC are sporadic; approximately 50% of those harbour somatic RET mutation. DLL3 is widely expressed in many neuroendocrine tumors and has been evaluated as a potential therapeutic target. Since stromal desmoplasia in sporadic MTC has been identified as a reliable predictor of aggressive behaviour and development of lymph node metastases, a possible correlation of DLL3 expression with the presence of stromal desmoplasia was of particular interest. 59 paraffin-embedded samples of sporadic MTC with (44 cases) and without (15 cases) stromal desmoplasia and known lymph node status were included. DLL3 expression was determined by immunohistochemistry; no expression (0%), low expression (1-49%) and high expression (≥ 50 %) were correlated with clinicopathological data. The proportion of DLL3 positivity was significantly correlated with both stromal desmoplasia (p < 0.0001) and lymph node metastases (p < 0.0001). MTC without stromal desmoplasia consistently lack DLL3 expression. This is the first study to focus on MTC regarding DLL3 expression and the relationship to various factors. Our results demonstrate that expression of DLL3 in MTC represents a reliable surrogate marker for stromal desmoplasia and lymph node metastases and might be an indicator for aggressive clinical behaviour. DLL3 expression in >50% of tumor cells virtually excludes MTC without stromal desmoplasia.DLL3 was discussed as a potential therapeutic target in malignant tumors of other locations with positive immunohistochemical reaction and might therefore be a new therapeutic option in MTC, as well.